2008
DOI: 10.1515/hf.2008.083
|View full text |Cite
|
Sign up to set email alerts
|

Fiberboard bending properties as a function of density, thickness, resin, and moisture content

Abstract: Fibers from treetop residues of lodgepole pine (Pinus contorta) and recycled old corrugated containers were used to fabricate wet-formed fiberboard panels over a range of densities from 300 to 1100 kg m -3 , a thickness range from 1.3 to 4.8 mm, and phenolic resin contents from 0% to 4.5%. The panels were then tested after conditioning in 50% and 90% relative humidity (RH) environments. Density, thickness, equilibrium moisture content, bending modulus of elasticity (MOE), and modulus of rupture (MOR) were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
3
5
0
Order By: Relevance
“…Similarly, Wu [17] showed that an improvement in MOR with raising the density of board. Such result is in agreement with others (Ganev et al, 2005;Hunt et al, 2008 andSantos et al, 2014) Also, it was noticed that the higher MOR value (234.6 kg/cm²) was attained in panels manufactured of 12 % resin. Such increase could be due an increase in bonded surface of OCCs and possibly due to OCCs surface coverage ratio increase with the resin (Young and Kim, 2007;Aryilmi andara,2012 andMalanit et al, 2009).…”
Section: Results and Discussion Mechanical Properties Modulus Of Rupture (Mor)supporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, Wu [17] showed that an improvement in MOR with raising the density of board. Such result is in agreement with others (Ganev et al, 2005;Hunt et al, 2008 andSantos et al, 2014) Also, it was noticed that the higher MOR value (234.6 kg/cm²) was attained in panels manufactured of 12 % resin. Such increase could be due an increase in bonded surface of OCCs and possibly due to OCCs surface coverage ratio increase with the resin (Young and Kim, 2007;Aryilmi andara,2012 andMalanit et al, 2009).…”
Section: Results and Discussion Mechanical Properties Modulus Of Rupture (Mor)supporting
confidence: 93%
“…The utilization of recovered paper as a raw material for MDF goods is a substantial means for decreasing waste and essential using resources (DE Alda and Torrea, 2006) .Thus, waste paper like OCCs can be transformed into variant design, that admits it to be enough for multiple usage implying composite boards manufactured throughout the process of (MDF) (Muehl et al,2004 andAyrilmis et al, 2008 )The process utilizes all the package of waste without remaining any OCCs residue are scraped into particles and produced in a layer to obtain a required thickness, then the mat is pressed under the heat and pressure (Buelens et al, 2001) .When fibers from recovered OCCs and Pinus contorta are utilized to manufacture fiberboard at range densities of 300 to 1100 kg/m 3 , (Hunt et al, 2008) found that increase density was associated with the increasing Internal Bonding (IB), Modulus Of Rapture (MOR) and Modulus Of Elasticity (MOE).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the MC was slightly lowered with increasing amount of pMDI. A slight decrease in moisture content with increasing amount of pMDI was observed in Hunt et al [ 55 ] for low density fiberboard which might be due to higher amount of pMDI-blocked OH-groups. The addition of propylene carbonate to pMDI resulted in a slightly lower moisture content which might be due to the enhanced spreading of the resin and, thus, a higher degree of blocked OH-groups on a larger surface area.…”
Section: Resultsmentioning
confidence: 84%
“…The pulp was wet-formed and hot-pressed to produce nominal 2.5 mm thick fiberboard. Binderless panels made from the OCC pulp fibers had very good mechanical properties (Hunt et al 2008). The NK was obtained from IMERYS Pigments & Additives Group, USA.…”
Section: Methodsmentioning
confidence: 99%
“…Each mat was placed between two screens and two 3.2 mm thick stainless steel cauls. The wet mats were hot pressed at 180 o C with continuous pressure (483 kPa) to target densities of 850 kg m -3 until the panels were dried (approximately 1% to 2% MC) (Hunt et al 2008). Final board thicknesses were between 2.7 to 2.9 mm thick.…”
Section: Methodsmentioning
confidence: 99%